2014
DOI: 10.5539/ass.v10n19p271
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Metacognitive Strategies to Develop Research Skills among Postgraduate Students

Abstract: Identifying a research problem is the most challenging aspect in teaching research skills at the postgraduate level. This action research project aimed to identify a suitable intervention to help students identify research problem in education setting and help them to write a sound research problem statement for their project. The study involves 51 postgraduate students in a research methodology course. The intervention was designed based on student-centered activities that include the use of metacognitive str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…A parallel finding was obtained in the previous study conducted by Tuncer and Yılmaz (2016) who demonstrated that there were positive but insignificant relations between metacognitive thinking skill and specific dimensions of scientific research self-efficacy. Rahman et al, (2014) evidenced that active implementation of metacognitive strategies played valuables role in developing planning, monitoring and evaluation skills of the identification process of a research problem. Beyer (1987) and Saemah et al, (2011) also emphasized that metacognitive skills developed students' research skills.…”
Section: Resultsmentioning
confidence: 99%
“…A parallel finding was obtained in the previous study conducted by Tuncer and Yılmaz (2016) who demonstrated that there were positive but insignificant relations between metacognitive thinking skill and specific dimensions of scientific research self-efficacy. Rahman et al, (2014) evidenced that active implementation of metacognitive strategies played valuables role in developing planning, monitoring and evaluation skills of the identification process of a research problem. Beyer (1987) and Saemah et al, (2011) also emphasized that metacognitive skills developed students' research skills.…”
Section: Resultsmentioning
confidence: 99%
“…The methodology utilized in this research is by using the non-experimental and quantitative design, in which metacognitive awareness inventory was derived from Rahman et al (2014) and Schraw and Dennison (1994) as a measurement to assess students' metacognitive awareness. Meanwhile, self-efficacy inventory was derived from May (2009) as a measure to assess students' self-efficacy.…”
Section: Methodsmentioning
confidence: 99%
“…Metacognitive awareness inventory was derived from Rahman et al (2014) and Schraw and Dennison (1994) as a measurement to assess students' metacognitive awareness. The measure had 30 questions that addressed two aspects of metacognitive awareness: cognitive regulation and metacognitive knowledge.…”
Section: Instrumentmentioning
confidence: 99%
“…The researcher used the Metacognitive Awareness Inventory developed by Schraw and Dennison (1994) and Rahman et al (2014). The instrument has 6-dimensional, and used the scale is a 5-point Likert type (1=Totally does not Agree, 5=Absolutely Agree).…”
Section: Scorementioning
confidence: 99%